The Imperial Underbelly: Workers, Contractors, and Entrepreneurs in Colonial India and Scandinavia - Gunnel Cederlöf (Routledge, 2023)
The volume introduces a new analysis of interconnected labour and economic history of colonial India and Scandinavia. From a recently found archive of a railway contractor's private and business papers, the studies revise both Indian labour history and Scandinavian modern history, and ties south Sweden into the British Empire. With deep insights into everyday work practices of Indian and European contractors and manual labourers, the book establishes a bridge across the globe, between two poor regions as sites of extraction and industrial transformation, resulting from global migration and capital flows. Drawing on rich archival sources such as the Joseph Stephens Archive, Maharashtra State Archives, the National Archives of India, and the British Library, the book offers deep insights into everyday business practices of European contractors in India, which were rarely documented and have remained largely inaccessible so far. A unique look into the labour and entrepreneurship practices under British colonial rule in India, as well as its impact on the most transformative years of modern southern Scandinavia, the book will be of great interest to students, academics, and teachers of history, labour studies, subaltern studies, colonialism, imperialism, economic history, railways, economics, and Scandinavian and South Asian studies.
Keywords: 330; Asian history; Colonialism and imperialism; Economic history; Transport industries; Industry and industrial studies